Padjadjaran Interest Inventory:Evaluation of Psychometric Properties - Yudiana, Whisnu; Reswara, Ilham Phalosa; Wiyono, Sudarmo; Purwono, R Urip (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This research aims to evaluate the psychometric properties of a new instrument for measuring vocational interest: Padjadjaran Interest Inventory (PII). There were 2,648 participants in this study, consisting of workers, high school, and university students, with gender proportion of 1,014 (38.3%) males and 1,634 (61.7%) females. This research used descriptive statistic test, t-test and MANOVA for gender differences, reliability coefficients and validity evidence by using confirmatory factor analysis (CFA). The results showed that PII has good psychometric properties: it has good reliability and valid internal structure; it is standardized by gender, and it is applicable for large groups with relative ease. PII can be used for career exploration. Limitation of this study was discussed for future research.